Judicial Oversight In Nigerian Society: The System Of Justice And Democracy, Issues, Prospects, And Solutions. - Sulaiman T.H; Abalaka, J.N; Ajiteru,S.A.R (International Journal of Law, Crime and Justice, 2025)
In recent years, the judiciary has faced harsh criticism for its tardiness in resolving electoral cases in a free and equitable way. Here, a Marxist theoretical approach is used to identify the issue contemplated. Every society's government should ideally endeavor to create a peaceful and habitable environment by enacting laws that safeguard the interests of its residents and those who live nearby. Since the judiciary, an arm of a democratic government, like the one in Nigeria, is tasked with upholding the law, it becomes quite concerning when this branch of the government is beset by charges and convictions of corruption. It was suggested that corrupt judges who commit crimes should face a variety of penalties and sanctions, including the death penalty, termination from their position, and public humiliation by being imprisoned for a period of time. Supporting politicians who buy off judges to see through, they ought to be tried and found guilty of bribing public officials. Additionally, they ought to be disqualified from any political office they are running for, since this will lessen judicial corruption, which impedes the development of Nigerian democracy. This report examines Nigeria's problems with corruption. It uses case studies of two nations with comparable issues and histories to provide a comparative perspective. Some of the suggested methods for an efficient performance of oversight functions include evolving reforms, guiding media and civil society engagement, and involving citizens.